2018
DOI: 10.1002/etep.2614
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for congestion management using improved differential evolution algorithm

Abstract: Summary This article proposes a new methodology for Congestion Management (CM) in a deregulated power system based on Generator Rescheduling/Load curtailment. This work utilizes 4 different sensitivity factors derived from the modified Jacobian matrix, used to identify the participating generator and loads for CM effectively. Also, a novel strategy of combining sensitivity factors and bidding costs is employed for selecting the control variables namely generator real power rescheduling, generator voltage adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The problem of congestion management is formulated as a non-linear optimal power flow problem with an objective of cost minimization for active power rescheduling by the generators and is given as. 14 Minimize n g ∑ i RC i .ΔP gi (17) subject to following constraints. 1.…”
Section: Problem Formulationmentioning
confidence: 99%
See 3 more Smart Citations
“…The problem of congestion management is formulated as a non-linear optimal power flow problem with an objective of cost minimization for active power rescheduling by the generators and is given as. 14 Minimize n g ∑ i RC i .ΔP gi (17) subject to following constraints. 1.…”
Section: Problem Formulationmentioning
confidence: 99%
“…But, still it lacks in an efficient model on the basis of rescheduling cost. So far, many research works are reported to address this issue 11‐17 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditional congestion management (CM) methods usually involve the construction of new power plants and/or transmission lines, which might be limited due to the high cost and the service duration for critical hours. [2][3][4] The CM problem has become more challenging in recent years due to the growth of renewable energy sources (RESs) and flexible loads. The incorporation of RESs into the power systems leads to some obstacles such as uncertainty and being far from demand centres for their efficient use.…”
mentioning
confidence: 99%